2017
DOI: 10.1111/tbed.12617
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of a novel highly pathogenic porcine reproductive and respiratory syndrome virus in China

Abstract: From 2014 to 2015, four novel highly pathogenic PRRS virus (HP-PRRSV) strains named 14LY01-FJ, 14LY02-FJ 15LY01-FJ, and 15LY02-FJ were isolated from high morbidity (100%) and mortality (40%-80%) in piglets and sows in Fujian Province. To further our knowledge about these novel virus strains, we characterized their complete genomes and determined their pathogenicity in piglets. Full-length genome sequencing analysis showed that these four isolates were closely related to type 2 (North American type, NA-type) is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 58 publications
2
40
1
Order By: Relevance
“…The most common pathogens detected in this study were IAV followed by Mhyo, which are also considered pathogens of major relevance in PRDC in other countries (Opriessnig et al., ). PRRS plays an important role in PRDC resulting in significant economic losses in North America, Europe and China (Choi et al., ; Liu et al., ; Sinn et al., ); however, in our study, PRRSV was not detected, consisted with Brazil's PRRS‐free status (Ciacci‐Zanella et al., ). Seventy per cent of the samples were from nursery pigs, the age group considered as at greatest risk for infections due to the waning of maternal antibodies (Van Reeth, Brown, & Olsen, ) and increased stress caused by intermingling of piglets from different farms, as part of the management practices in Brazilian swine production system.…”
Section: Discussioncontrasting
confidence: 64%
“…The most common pathogens detected in this study were IAV followed by Mhyo, which are also considered pathogens of major relevance in PRDC in other countries (Opriessnig et al., ). PRRS plays an important role in PRDC resulting in significant economic losses in North America, Europe and China (Choi et al., ; Liu et al., ; Sinn et al., ); however, in our study, PRRSV was not detected, consisted with Brazil's PRRS‐free status (Ciacci‐Zanella et al., ). Seventy per cent of the samples were from nursery pigs, the age group considered as at greatest risk for infections due to the waning of maternal antibodies (Van Reeth, Brown, & Olsen, ) and increased stress caused by intermingling of piglets from different farms, as part of the management practices in Brazilian swine production system.…”
Section: Discussioncontrasting
confidence: 64%
“…KEYWORDS CD83, NF-B, PRRSV, Sp1, nonstructural protein 10, nucleocapsid O ver the last 3 decades, porcine reproductive and respiratory syndrome virus (PRRSV) has become a serious threat to the swine industry worldwide (1,2). Current vaccines do not provide complete protection against this disease (3)(4)(5), and it is unclear how PRRSV inhibits the host's immune response and induces persistent infection.…”
mentioning
confidence: 99%
“…reported that HNjz15 inoculated piglets display mild clinical manifestations and that HNjz15 is less pathogenic than the JXA1 and JL580 PRRSV strains (Sun et al., ). Subsequently, the NADC30‐like PRRSV strains, such as 14LY01‐FJ, 14LY02‐FJ, 15LY01‐FJ and 15LY01‐FJ, originating from JXA1‐like PRRSV, induce a similar clinical symptom which is caused by HP‐PRRSV in piglets (Liu et al., ). Collectively, recombination may accelerate evolution and influence the virulence of NADC30‐like PRRSV.…”
Section: Discussionmentioning
confidence: 99%